'Those same cursed Saracens': Charlemagne's campaigns in the Iberian Peninsula as religious warfare. Issue 4 (7th August 2016) - Ottewill-Soulsby, Samuel
Abstract : While it is well known that many of Charlemagne's wars had a strong religious element, Frankish campaigns against the Muslims of Spain in his reign have generally been understood as secular exercises in power politics. This article presents evidence contemporary to Charlemagne's reign to argue against this, using a diverse range of sources to conclude that many observers of the Frankish invasions of the Iberian Peninsula understood them as religious wars aimed both at the defending of Christian communities in Francia and protecting and expanding the worship of Christianity in Spain. Further, although the prosecution of these wars was politically opportunistic, the sources suggest that Charlemagne and his court encouraged interpretations of these campaigns in religious terms and that they might be considered examples of religious war.